An Efficient Key Scheme for Layered Access Control of MPEG-4 FGS Video - Zhu, Bin Benjamin; Feng, M.; Li, S. (Institute of Electrical and Electronics Engineers, Inc., 2004)
The recently proposed Scalable Multi-Layer FGS Encryption (SMLFE) [4][5] encrypts an MPEG-4 FGS stream into multiply PSNR and bitrate quality layers for layered access control. Both layer types are supported simultaneously. A simple key scheme was used in SMLFE. In this paper, we propose a novel key scheme for SMLFE that reduces the number of keys maintained and managed by a license server for each protected MPEG-4 FGS stream to two. The new key scheme needs only one key contained in a license to be sent to a consumer. This scheme is based on a cryptographic secure hash function and the Diffie- Hellman key agreement. It satisfies all the requirements of SMLFE and can be used to replace the original simple key scheme for SMLFE. The secure one-way hash and intractability of the Diffie-Hellman and the related problems of computing discrete logarithm ensure the security of the new key scheme.